MANAJEMEN LABORATORIUM ILMU PENGETAHUAN ALAM (Tinjauan Khusus Fungsis Manajemen di Sekolah Menengah Pertama Negeri 6 Kota Pekanbaru ) - Resti Yolanda; Azhar Azhar; Marzuki Marzuki (Universitas Riau, 2019)
This method aims for the function of laboratory management of Natural Sciences at State Junior High School 6 Pekanbaru City. The type of data of this research is using primary data. Research data were obtained from principals, laboratory heads, and science teachers. Data collection techniques are interviews, observation and documentation. The instrument of this researcher is the researcher himself by applying interview guides, observation checklists, and documentation. Data analysis technique is field analysis and result analysis with process (1) data reduction, (2) data presentation, (3) drawing conclusion. The results of this study indicate that the science of laboratory management in SMP Negeri 6 Pekanbaru City already meet the standard labpratorium IPA, commencement of laboratory facilities that are complete, laboratory conditions adequate although there are still some laboratory space that is not feasible to use, has an organizational structure despite the absence of laboratory labor.